Effect of denosumab on bone mineral density in Japanese women with osteopenia treated with aromatase inhibitors for breast cancer: subgroup analyses of a Phase II study - Nakatsukasa K; Koyama H; Ouchi Y; Sakaguchi K; Fujita Y; Matsuda T; Kato M; Konishi E; Taguchi T (Dove Medical Press, 2018)
Katsuhiko Nakatsukasa,1 Hiroshi Koyama,2 Yoshimi Ouchi,1 Kouichi Sakaguchi,1 Yoshifumi Fujita,1 Takayuki Matsuda,3 Makoto Kato,4 Eiichi Konishi,5 Tetsuya Taguchi1 1Department of Endocrine and Breast Surgery, Kyoto Prefectural University of Medicine, Kyoto, Japan; 2Department of Breast Surgery, Nara City Hospital, Nara, Japan; 3Department of Breast Surgery, Saiseikai Kyoto Hospital, Kyoto, Japan; 4Department of Breast Surgery, Kato Breast Surgery Clinic, Kyoto, Japan; 5Department of Surgical Pathology, Kyoto Prefectural University of Medicine, Kyoto, Japan Background: The aim of the study was to conduct subgroup analyses of therapeutic effects of 12-month denosumab therapy on the percentage change in bone mineral density (BMD) from baseline in the lumber spine and femoral neck. Materials and methods: We prospectively evaluated the BMD of the lumbar spine and femoral neck of 100 hormone receptor-positive, clinical stage I–IIIA postoperative postmenopausal breast cancer patients, for whom treatment with aromatase inhibitors (AIs) as adjuvant endocrine therapy was scheduled. The primary endpoint was the percent change in lumbar spine BMD from baseline to 12 months. Patient subgroups were analyzed according to baseline variables that are known risk factors for bone loss, including previous AI therapy, age, time since menopause, baseline body mass index (BMI), and baseline BMD T-score. Results: At 12 months, lumbar spine BMD increased by 4.7%; the patients who were administered AI therapy prior to denosumab (n=70) demonstrated a 4.7% increase in BMD, and the patients who received denosumab at the start of AI therapy (n=30) demonstrated a 4.5% increase in BMD (p=0.8385). Additionally, 2.4% and 1.4% increases in BMD of the right and left femoral neck, respectively, were observed. Initiation of AI (with denosumab, before denosumab), type of AI (non-steroidal, steroidal), age (<65, ≥65 years), time since menopause (≤5, >5 years), BMI (<25, ≥25 kg/m2), and T-score (≤-1.0, >-1.0) of the right femoral neck were as follows: (2.2%, 2.5%, p=0.7773), (2.6%, 0.9%, p=0.1726), (2.5%, 2.3%, p=0.7594), (2.1%, 2.4%, p=0.2034), (2.1%, 2.9%, p=0.2034), and (2.3%, 2.7%, p=0.6823), respectively. Initiation of AI (with denosumab, before denosumab), type of AI (non-steroidal, steroidal), age (<65, ≥65 years), time since menopause (≤5, >5 years), BMI (<25, ≥25 kg/m2), and T-score (≤-1.0, >-1.0) of the left femoral neck were as follows: (1.0%, 1.5%, p=0.1972), (1.2%, 2.7%, p=0.2931), (1.4%, 1.3%, p=0.8817), (-0.1%, 1.6%, p=0.1766), (1.3%, 1.9%, p=0.6465), and (1.5%, 1.1%, p=0.6573), respectively. Conclusion: Twice-yearly treatment with denosumab was associated with increased BMD among Japanese women receiving adjuvant AI therapy, regardless of the baseline characteristics or skeletal site. Keywords: aromatase inhibitor, denosumab